PENDAMPINGAN FANDOMPRENEUR DALAM MEMANFAATKAN MEDIA DIGITAL UNTUK PROMOSI PENJUALAN MERCH K-POP - Paramita, Sinta; Laila, Kumi (Jurnal Serina Abdimas, 2023)
ABSTRACT The presence of the Korean Pop industry or what is known as K-Pop does not only provide entertainment for the people, but also brings in coffers of income, especially for fans. As the Korean Wave (K-Pop fans) increases in society, more and more fans are competing to open business opportunities by selling K-Pop idol merch. There are those who sell official merch, there are also those who sell merch made by themselves such as tote bags, t-shirts, hoodies, stickers, and many more. Even though K-Pop fans are potential land for the K-Pop merch business, in fact there are still many fandompreneurs (fans who own K-Pop merch businesses) who have difficulty selling merch. Therefore the PKM Fikom Untar Team is trying to help provide creative communication training for Fandompreneurs to utilize social media as a media for promotion or sales. The team plans to provide assistance with the theme of Social Media Utilization Training as a means of promoting sales of K-Pop Merch for Fandompreneurs in West Jakarta. This activity also collaborates with digital media practitioners and consultants in providing assistance. As a result of these mentoring activities, Soul Project began creating content with various communication mixes such as Instagram, TikTok and the Website to expand product information and marketing.